High risk electrocardiographic patterns in patients with acute coronary syndrome - Echeverri-Marín, Diego (2020)
Acute myocardial infarction is the leading cause of death in the world and the electrocardiogram remains the diagnostic tool for determining an acute myocardial infarction with ST-segment elevation. In spite of this, only half of the patients present classic electrocardiogram findings compatible with the ST-elevation infarction criteria. There is a spectrum of electrocardiographic findings that may reflect a phenomenon of acute coronary occlusion, which should be promptly recognized by the clinician to offer early reperfusion therapy.